Knowledge of Breastfeeding Mothers About Early Childhood Caries (ECC) Prevention Based on Socioeconomic Status (A Study at the Maternal and Child Health Clinic Periuk Jaya Health Center, Tangerang City) - Faradilla Rachmasari; Annisa Septalita (Scientific Dental Journal, 2025)
Background: Early Childhood Caries is a major health issue in Indonesia, with a prevalence of 67.3% according to the 2018 RISKESDAS, particularly in Banten, where the prevalence is 39.2%. The role of breastfeeding mothers is crucial in the prevention of ECC, especially in avoiding practices that can increase the risk of dental caries in children, such as the discouraged practice of giving milk through a bottle before bedtime. ECC is also influenced by the socioeconomic status of the family, including the type of occupation, income, and level of education, all of which have a considerable impact on the prevalence of ECC. Objective: To determine the knowledge of breastfeeding mothers regarding the prevention of Early Childhood Caries (ECC) based on socieoeconomic status. Methods: The type of research used is descriptive quantitative, with a sampling technique of quota sampling. A questionnaire was given to the respondents, consisting of sociodemographic questions and 8 questions regarding breastfeeding mothers' knowledge about the prevention of ECC. Results: The average age of breastfeeding mothers is 27.81±4.5 years, with the majority having a high school education, an income equivalent to the regional minimum wage (UMR), and working as employees. The average knowledge score of breastfeeding mothers regarding ECC prevention is 4.5±1.4, with 47 mothers having low knowledge and 50 mothers having high knowledge. Breastfeeding mothers with higher education, income at or above the UMR, and those who work as employees tend to have higher knowledge regarding the prevention of ECC. Conclusion: The level of knowledge of breastfeeding mothers regarding ECC prevention shows almost the same proportion between high and low levels of knowledge. Breastfeeding mothers who work as employees, have a higher level of education and income, have higher knowledge about preventing ECC.